Enhanced sensitivity of an antibody competitive blocking enzyme-linked immunosorbent assay using Equine arteritis virus purified by anion-exchange membrane chromatography. (November 2015) - Chung, Chungwon J.; Grimm, Amanda L.; Wilson, Carey L.; Balasuriya, Udeni B. R.; Chung, Grace; Timoney, Peter J.; Bandaranayaka-Mudiyanselage, Chandima-Bandara; Lee, Stephen S.; McGuire, Travis C.
In an effort to improve a competitive blocking enzyme-linked immunosorbent assay (cELISA) for antibody detection to Equine arteritis virus (EAV), antigen purified by anion-exchange membrane chromatography capsule (AEC) was evaluated. Virus purification by the AEC method was rapid and easily scalable. A comparison was made between virus purified by the AEC method with that obtained by differential centrifugation based on the following: 1) the relative purity and quality of EAV glycoprotein 5 (GP5) containing the epitope defined by monoclonal antibody 17B7, and 2) the relative sensitivity of a commercial antibody cELISA with the only change being the 2 purified antigens. On evaluation by Western blot using GP5-specific monoclonal antibody 17B7, the AEC-purified EAV contained 86% GP5 monomer whereas the differentially centrifuged EAV contained <29% of the monomer. Improvement of analytical sensitivity without sacrifice of analytical specificity was clearly evident when cELISAs prepared with EAV antigen by each purification method were evaluated using 7 sensitivity and specificity check sets. Furthermore, the AEC-purified EAV–based cELISA had 30–40% higher agreement with the virus neutralization (VN) test than the cELISA prepared with differentially centrifuged EAV based on testing 40 borderline EAV-seropositive samples as defined by the VN test. In addition, the AEC-purified cELISA had highly significant ( P = 0.001) robustness indicated by intra-laboratory repeatability and interlaboratory reproducibility when evaluated with the sensitivity check sets. Thus, use of AEC-purified EAV in the cELISA should lead to closer harmonization of the cELISA with the World Organization for Animal Health–prescribed VN test.